IMPLEMENTASI STRATEGI KOMUNIKASI PEMASARAN TERPADU MAYBANK BALI MARATHON 2017 - Yudena, Aulia Bunga; Alit Suryawati, I Gusti Agung; Pascarani, Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRA CT   Marketing communication is a driving factor for success within a company, to introduce companies and establish relationships with consumers. One effort that can be done by the company as a form of innovation from the development of communication technology to gain the trust of the community is to hold certain activities. PT Bank Maybank Indonesia as a bank that supports the lifestyle of people who like sports, especially running sports, makes an activity namely Maybank Bali Marathon (MBM). This research was conducted to find out how the integrated marketing communication strategy of the Maybank Bali Marathon Corporate Communication Division was in carrying out the Maybank Bali Marathon 2017. The research was a qualitative - descriptive study using data collection techniques in the form of interviews and document studies. The results of this study indicate that MBM uses an integrated marketing communication strategy (IMC) centrally. In addition, the marketing communication activities carried out by MBM focus more on social media (online) compared to offline activities. Keywords: communication strategy, integrated marketing communication, Maybank Bali Marathon